On Common Fixed Point Theorems for Generalized Contractions Involving Rational Expressions and Auxiliary Functions (European Journal of Pure and Applied Mathematics, 2025)
The purpose of this article is to prove common fixed point theorems for pair of maps (not necessary continuous), satisfying generalised contractions involving rational expressions and auxiliary functions $(ψ, β)$ in the setting of both fuzzy $b$-metric spaces as well as partially ordered fuzzy $b$-metric spaces. To substantiate our finding, an example with graphical representation is given. The obtained results may generalize and improve some of the well-known fixed-point results of the literature.
Keywords: auxiliary functions; rational expression; partially ordered